Indonesian Unity for Equitable and Fair Health Policy - Tude, Ryan (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2025)
This article examines the contribution of Indonesia’s value of unity to the development of inclusive health policies. Using a literature review approach, the study explores how the principle of unity, as articulated in Pancasila, particularly its third principle (Persatuan Indonesia), functions as both an ethical foundation and a practical guideline in shaping policies that respond to Indonesia’s diverse society. The analysis highlights the role of Pancasila in influencing the formulation of inclusive health policies, especially in addressing disparities arising from geographical, cultural, and socioeconomic conditions. The findings suggest that the value of unity plays a crucial role in promoting equitable access to healthcare services and strengthening policy coherence in the pursuit of inclusive national development.